Occurrence and diversity of entomopathogenic fungi in cultivated and uncultivated soils in Pakistan. Issue 1 (18th January 2013) - Wakil, Waqas; Ghazanfar, M. Usman; Riasat, Tahira; Kwon, Young Jung; Qayyum, Mirza Abdul; Yasin, Muhammad
Abstract The distribution of entomopathogenic fungi in various geographical areas of Punjab, Pakistan, is poorly understood. The present study was planned to explore the occurrence and diversity of entomopathogenic fungi from soils collected from cultivated and non‐cultivated habitats. The detailed survey of different habitats (crop fields, fruits, vegetables, forests) was conducted to collect soil samples and the associated fungi were isolated using Galleria bait method. Among 210 soil samples, 168 fungal isolates were recovered and identified, with 98 from forests, 32 from vegetables, 30 from field crops and 8 from fruits. The major entomopathogenic fungi recovered from these samples were Beauveria bassiana, Metarhizium anisopliae, Paecilomyces lilacinus, B. brongniartii, P. chlamydosporia and Lecanicillium attenuatum. The diversity of entomopathogenic fungi was greater in soil samples from forests compared to crop fields, vegetables and fruits, respectively. The geographical attributes (altitude, longitude, latitude) greatly influenced the occurrence of entomopathogenic fungi with the highest number of isolates found from >600 m altitude, 33°–34′N latitude, and 73°74′E longitude from soil samples. The results of the surveys clearly indicated that the entomopathogenic fungi are distributed in the soils which may be used in successful IPM programs in future.